Potential of Curcuma Temulawak Extract on Melatonin and Hyaluronidase Levels in Human Skin Fibroblast Cell Line Exposed to UV Light as an Aging Model - Lumbantobing, Eva Christine Natalia; Chiuman, Linda; fachrial, Edy (South Eastern European Journal of Public Health, 2025)
Skin aging is characterized by a decrease in the skin's ability to regenerate and maintain its structure, which is influenced by endogenous factors (genetic mutations, hormonal factors) and exogenous factors (UV exposure, pollution). UV radiation accelerates skin aging by generating reactive oxygen species (ROS) that can activate hyaluronidase and induce inflammation, leading to cell apoptosis. Natural antioxidants such as melatonin play an important role in skin protection, but melatonin levels decrease with UV exposure. The temulawak plant contains compounds that can be utilized as antioxidants. This study aims to determine the potential of Curcuma xanthorrhiza (temulawak) natural extract to reduce UV-induced skin aging by increasing melatonin levels and reducing hyaluronidase activity. Extraction was performed using maceration method with 70% ethanol solvent. Aging model cells were prepared from human skin fibroblast cell cultures that were exposed to UV light 300J/cm2 for 75 minutes. The treatment given to the aging model cells, namely temulawak extract in 3 different concentrations 12.50; 6,25; 3.13 μg/mL. The results showed that temulawak extract significantly increased melatonin level in fibroblasts exposed to UV light, with an optimal concentration of 12.25 µg/mL (147.71 pg/mL metionin). In addition, temulawak extract also significantly reduced hyaluronidase levels with the same optimal concentration (95.78 ng/mL). Curcuma longa extract may serve as an effective natural agent for anti-aging skin care products by increasing melatonin levels and reducing hyaluronidase activity, thus potentially improving skin health and reducing the effects of aging caused by UV exposure.